A fast and reliable approach to simulating the output from an x-ray tube used for developing security backscatter imaging - Vella, Anna; Munoz, Andre Arelius Marcus; Healy, Matthew J. F.; Lane, David W.; Lockley, David; Zhou, J. G. (SPIE - International Society for Optics and Photonics, 2017)
The PENELOPE Monte Carlo simulation code was used alongside the SpekCalc code to simulate X-ray energy spectra from a VJ Technologies’ X-ray generator at a range of anode voltages. The PENELOPE code is often utilised in medicine but is here applied to develop coded aperture and pinhole imaging systems for security purposes. The greater computational burden of PENELOPE over SpekCalc is warranted by its greater flexibility and output information. The model was designed using the PENGEOM sub-tool and consists of a tungsten anode and five layers of window materials. The photons generated by a mono-energetic electron beam are collected by a virtual detector placed after the last window layer, and this records the spatial, angular and energy distributions which are then used as the X-ray source for subsequent simulations. The process of storing X-ray outputs and using them as a virtual photon source can then be used efficiently for exploring a range of imaging conditions as the computationally expensive electron interactions in the anode need not be repeated. The modelled spectra were validated with experimentally determined spectra collected with an Amptek X-123 Cadmium Telluride detector placed in front of the source.
Copyright 2017 Society of Photo-Optical Instrumentation Engineers. One print or electronic copy may be made for personal use only. Systematic reproduction and distribution, duplication of any material in this paper for a fee or for commercial purposes, or modification of the content of the paper are prohibited.